2008
DOI: 10.1021/ma801798p
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for Efficient Postpolymerization Functionalization of Regioregular Polythiophenes

Abstract: Contents 1. General Experimental Methods 2. Experimental Procedures 2.1 Monomer Syntheses 2.2 Polymerization Procedures 2.3 Optimization of "Click-Chemistry" for Ethynyl-Terminated Poly(3-hexylthiophene) 2.4 Model Compound for End "Clicking" Reactions 2.5 Synthesis of Naphthalenediimides 2.6 Application of "Click-Chemistry" Conditions to Post-Polymerization Side-Chain Functionalization 3. NMR Spectra 4. Supplementary GPC Data 5. Supplementary UV-vis Data S2 General Experimental MethodsAll chemicals were purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…were also synthesized [45][46][47][48][49][50]. Although no detailed study on the polymerization mechanism was reported, the polymerization may also follow chain-growth mechanism.…”
Section: Pt4-pt9mentioning
confidence: 99%
See 2 more Smart Citations
“…were also synthesized [45][46][47][48][49][50]. Although no detailed study on the polymerization mechanism was reported, the polymerization may also follow chain-growth mechanism.…”
Section: Pt4-pt9mentioning
confidence: 99%
“…Although no detailed study on the polymerization mechanism was reported, the polymerization may also follow chain-growth mechanism. The polymerization for PT5 has to be carried out at 70 °C [46]. At low temperature such as room temperature used in the preparation of P3HT, very little of the targeted polymer was obtained.…”
Section: Pt4-pt9mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In the early part of this century, a significant breakthrough came from the work of McCullough et al and Yokozawa et al They independently developed the well-defined Kumada catalyst transfer polymerization (KCTP) to prepare P3HT with the high regioregularity, predictable molecular weight, and controlled terminal structure. [4][5][6][7] The discovery of this innovative methodology opens the door for the preparation of block copolymers, 8,9 alternating copolymers, 10 polymer brushes 11 to name a few. In the KCTP, 2,5-dibromo-3-hexylthiophene or 2-bromo-3-hexyl-5-iodothiophene is firstly subjected to the halogen-metal exchange reaction with RMgCl to generate 2-bromo-5-chloromagnesio-3-hexylthiophene in the moderate to high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many examples of rod-coil P3HT-based BCPs , all conjugated rod-rod P3HT-based BCPs [41][42][43][44][45][46][47][48][49][50][51][52] are still less focused on and limited only to diblock copolythiophene derivatives, regardless of the expectation of high performance as semiconductors, due to the absence of insulating coil segments. Two exceptional examples of well-defined all conjugated rod-rod BCPs, P3HT-b-poly(2,6-dialkoxyphenylene) [53] and P3HT-b-poly(9,9-dioctylfluorene) [54], were very recently synthesized, comprised of different conjugated backbone structures, based on sequential quasi-living GRIM polymerization.…”
Section: Introductionmentioning
confidence: 99%